Modern poetry, popular song and their dangerous liaisons. Issue 3 (3rd July 2018) - Hideto, Tsuboi; Murphy, Alexander
Abstract: In this article, Tsuboi Hideto examines the mutually entwined pursuits of modern poetry and music in interwar Japan, focusing especially on the work of Nakahara Chūya, Kitahara Hakushū, and the People's Poetry group. Cutting across their respective distinctions within the poetry establishment, Tsuboi draws attention to these figures' shared investment in symphonic, folk and popular music. In so doing, he identifies among them a prevailing concern for curating a poetic voice that might harmonize the conflictual registers of individual and collective expression and thereby attune the work of the poet to that of the 'people' more broadly. Meanwhile, the essay traces the currents of modernist and avant-garde thought in Japan and Europe that framed these poets' engagements with music and sound. Tsuboi then illustrates the varying degrees to which these voices, forged within the cosmopolitan milieu of the Taisho period, bent toward the nationalizing project and later gave way to the chorus of wartime fascism and imperial expansion.